Mechanical and microstructural properties of ultra-translucent dental zirconia ceramic stabilized with 5 mol% yttria. (November 2020) - Harada, Akio; Shishido, Shunichi; Barkarmo, Sargon; Inagaki, Ryoichi; Kanno, Taro; Örtengren, Ulf; Egusa, Hiroshi; Nakamura, Keisuke
Abstract: Monolithic dental prostheses fabricated from 3 mol.% yttria-stabilized zirconia (3YZ) are becoming increasingly popular. Recently, 5 mol.% yttria-stabilized zirconia (5YZ) which significantly improves the translucency of 3YZ has been prepared. However, its mechanical and microstructural properties, especially those affected by low-temperature degradation (LTD), have not been fully elucidated yet. The objective of the present study was to establish the relationship between the flexural strength of 5YZ with or without autoclave-induced LTD and its microstructural properties. For this purpose, a total of 320 bar-shaped specimens were cut from 5YZ and 3YZ blocks, and half of the specimens in each group were autoclaved at 134 °C for 50 h. Their flexural strengths were determined by conducting three-point bending tests, and the obtained results were analyzed by the Weibull statistical method. Grain sizes and crystalline structures of the specimens were analyzed by scanning electron microscopy (SEM) and X-ray diffraction, respectively. Additionally, the LTD-induced phase transformation was examined by Raman microscopy and cross-sectional surface analysis. The characteristic strengths of 5YZ and 3YZ were approximately 620 and 950 MPa, respectively, and 5YZ was found to be more resistant to LTD in terms of phase transformation than 3YZ. However, a low amount of the monoclinic phase was detected even in 5YZ after 50 h of autoclaving, which significantly decreased its flexural strength and reliability. The results of SEM analysis revealed that 5YZ was composed of two distinct regions: a dominant matrix with large grains (median size: 0.8 μm) and scattered areas with small grains (median size: 0.4 μm). Phase transformation analysis and fractography data indicated that the small-grain region was strongly affected by LTD and likely represented a fracture origin. The described properties should be considered during the clinical application of monolithic 5YZ dental prostheses. Graphical abstract: Image 1 Highlights: Zirconia ceramics stabilized with 5 and 3 mol.% yttria (5YZ and 3YZ) are examined. The flexural strength of 5YZ is approximately 330 MPa lower than that of 3YZ. Low-temperature degradation decreases the flexural strengths of both 3YZ and 5YZ. 5YZ is composed of a matrix with large grains and scattered spots with small grains. The monoclinic phase formed on the 5YZ surface can be a fracture origin.